2021
DOI: 10.1111/jcmm.16774
|View full text |Cite
|
Sign up to set email alerts
|

Carbofuran affects cellular autophagy and developmental senescence through the impairment of Nrf2 signalling

Abstract: Senescence is a cellular response towards various stresses, characterized by the permanent proliferative arrest on cells. 1 Pharmacological and/or genetic ablation of senescence/senescent cells improve health outcomes and extend the lifespan. 2 Autophagy is a lysosome-mediated cellular catabolic process, implicated with cellular senescence. In regulating the cellular homeostasis, autophagy usually suppresses cellular senescence by eliminating damaged cytoplasmic organelles and macromolecules. 3 In contrast, au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…Moreover, prolonged ROS production activates the NRF2/antioxidant responsive element (ARE) pathway, implicated in detoxification, through NRF2 phosphorylation and translocation to the nucleus, leading to transcription regulation of NRF2 target genes. Several of these genes are involved in the antioxidant response, such as Cat , Sod-1 , and Hmox-1 among others [ 63 , 64 , 65 ]. Some evidence shows that cellular senescence is directly associated with NRF2 pathway impairment, since overactivation of the NRF2 pathway decreases the expression of some senescence markers, such as p21 [ 63 ], whereas NRF2 inhibition produces cellular senescence [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, prolonged ROS production activates the NRF2/antioxidant responsive element (ARE) pathway, implicated in detoxification, through NRF2 phosphorylation and translocation to the nucleus, leading to transcription regulation of NRF2 target genes. Several of these genes are involved in the antioxidant response, such as Cat , Sod-1 , and Hmox-1 among others [ 63 , 64 , 65 ]. Some evidence shows that cellular senescence is directly associated with NRF2 pathway impairment, since overactivation of the NRF2 pathway decreases the expression of some senescence markers, such as p21 [ 63 ], whereas NRF2 inhibition produces cellular senescence [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several of these genes are involved in the antioxidant response, such as Cat , Sod-1 , and Hmox-1 among others [ 63 , 64 , 65 ]. Some evidence shows that cellular senescence is directly associated with NRF2 pathway impairment, since overactivation of the NRF2 pathway decreases the expression of some senescence markers, such as p21 [ 63 ], whereas NRF2 inhibition produces cellular senescence [ 64 ]. Different preclinical studies have demonstrated an impairment of the NRF2 antioxidant pathway in CKD.…”
Section: Discussionmentioning
confidence: 99%
“… 32–35 SPNS1, which encodes Spinster homologue 1 protein, is a transmembrane protein that can modulate the metabolism of autophagic lysosomal and critically associate with cellular ageing and survival. 36 37 Notably, SPNS1 has recently been considered as a core component of T cell receptor signalling. 38 A slew of studies have shown that TRIM10 and TRIM27 were involved in several inflammation processes.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from this, ZNF322 can regulate the expression of two cell-cycle genes ( P27 and CDK2 ), which were characterised as crucial regulators involved in synoviocytes proliferation 32–35 . SPNS1, which encodes Spinster homologue 1 protein, is a transmembrane protein that can modulate the metabolism of autophagic lysosomal and critically associate with cellular ageing and survival 36 37. Notably, SPNS1 has recently been considered as a core component of T cell receptor signalling 38.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, prolonged ROS production activates the NRF2/Are pathway, implicated in detoxification, through NRF2 phosphorylation and translocation to the nucleus, leading to the regulation of transcription of NRF2 target genes. Several of these genes are involved in the antioxidant response, such as Catalase, Sod-1, Hmox-1 and others (Khan et al, 2021;Ungvari et al, 2019;Yu et al, 2021). Some evidences show that cellular senescence is directly associated with NRF2 pathway impairment, since increased NRF2 pathway decreases senescence marker expression such as p21 (Yu et al, 2021) and its inhibition produces cellular senescence (Khan et al, 2021).…”
Section: Figure 10 Conceptual Representation Of Age-associated Mechan...mentioning
confidence: 99%